Pengaruh Zakat Produktif, Pengembangan Keterampilan dan Pendampingan Usaha terhadap Minat Wirausahawan Kuliner pada Masa Pandemi: - Ghina Sabrina; Ali Idrus (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to determine the effect of productive zakat, skill development, and business assistance on the interest of culinary entrepreneurs during the pandemic. The researchers used quantitative methods with primary data collection techniques in the form of questionnaires distributed to 33 respondents via Google Forms. The data analysis technique used is multiple linear regression using SPSS version 23. The results of the t-test indicate that the significance value of the productive zakat variable is 0.008 which is greater than 0.05, meaning that there is no significant effect of productive zakat on the interest of culinary entrepreneurs. The significance value of the skill development variable is 0.000, smaller than 0.05, meaning that there is a significant influence between skill development on the interest of culinary entrepreneurs. The significance value of the business mentoring variable is 0.249, which is greater than 0.05, meaning that there is no significant effect between business mentoring and culinary entrepreneurs. The results of the F test obtained a significant value of 0.000 meaning that the value is smaller than the standard significance level that has been set at 0.05, it can be concluded that productive zakat, skills development, and business assistance simultaneously affect the interest of culinary entrepreneurs. And the results of the coefficient of productive zakat, skill development, and business assistance have an effect of 94%, and the remaining 6% are not explained in this research model Keywords: Productive Zakat, Skills Development, and Business Assistance on the Interests of Culinary Entrepreneurs During a Pandemic.